A genre-based approach to writing across the curriculum in isiXhosa in the Cape Peninsula schools - Mali-Jali, Nomfundo (Stellenbosch : University of Stellenbosch, 2008)
Thesis (DLitt (African Languages))--University of Stellenbosch, 2007.